The humidity effect on turbulent convection in a vertical channel. (31st August 2006) - Muresan, C.; Bennacer, R.; Menezo, C.; Vareilles, J.; , S. Julien
A numerical investigation of turbulent convective flows transporting humidity in a vertical heated channel is carried out. The governing equations associated to κ-ε low Reynolds models are solved in a two-dimensional domain using a control volume method and the SIMPLER algorithm for the P-V coupling. The analysis focuses on the humidity effect on the flow and resulting heat transfer. The considered wet wall induces humidity effect and modifies the obtained chimney effect. The thermal and humidity buoyancy act in opposite direction, so the resulting mass flow decreases. The water evaporation modifies significantly the temperature field and the apparent heat transfer.